KOMPETENSI GURU DAN MOTIVASI MENGAJAR GURU BERPENGARUH TERHADAP EFEKTIVITAS PEMBELAJARAN DI SMK NEGERI 3 KOTA SERANG - Dewi Surani; Mifthahudin Mifthahudin (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2018)
This research to find out the influence of teacher competence and motivation in teaching towards the effectiveness of learning at SMK Negeri 3 Serang City. This research used quantitative approach with survey method with 53 teachers as samples. The samples were taken by a saturated sampling technique in which the total population was sampled. Data analysis techniques use classical assumption test, multiple linear regression and coefficient of determination analysis. The results showed that: (1) Teachers professional competence influence the effectiveness of learning with the determination coefficient 0.189 or 18.9%. (2) Teaching motivation influence the effectiveness of learning with the determination coefficient 0.388 or 38.8%. and (3)Teachers profesional competence and Teaching motivation influence simultaneously toward the effectiveness of learning with the value of coefficient determination 455 or 45.50%. Keywords. Teacher competence, teacher teaching motivation, effectiveness of learning